2008
DOI: 10.1590/s0066-782x2008001500010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de doença arterial coronariana e avaliação pré-operatória em portadores de valvopatia

Abstract: SummaryBackground: Coronary angiography has been indicated in the preoperative phase for patients with valvopathy over 35 years of age. However, the actual prevalence of obstructive coronary artery disease (CAD) in this population has been little studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Sampaio et al have reported a prevalence of 3.42% in a sample of 3736 patients with a mean age of 43.7 years. 12 Kruczan et al 11 have shown a global prevalence of obstructive CAD of 15.9%, 6% in patients aged less than 50 years.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sampaio et al have reported a prevalence of 3.42% in a sample of 3736 patients with a mean age of 43.7 years. 12 Kruczan et al 11 have shown a global prevalence of obstructive CAD of 15.9%, 6% in patients aged less than 50 years.…”
Section: Discussionmentioning
confidence: 97%
“… 7 It usually affects young individuals, who have less risk factors for atherosclerosis, and, thus, lower prevalence of obstructive CAD. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…The fact that preoperative invasive procedures such as coronary artery bypass grafting or percutaneous coronary angioplasty do not reduce perioperative risk in patients with significant stable CAD is highlighted (7,10). These findings also reinforce that the request for these preoperative exams results in over-diagnosis with subsequent unnecessary treatments, without a solid evidence base that the outcome is positive considering benefits, costs, and possible damages (11,14,29).…”
Section: Discussionmentioning
confidence: 94%
“…A common practice emerging from these evaluations is the pursuit of the diagnosis of silent coronary disease (screening), motivated by the belief that this would generate cardiovascular protection for patients. Although this approach generates a sense of safety in patients with negative results, positive results promote a cascade of conduct that not only fail to attenuate the risk of cardiovascular events (7,9,10), but may lead to undesirable outcomes, ranging from suspension of surgery to inappropriate revascularization and adverse events resulting from overdiagnosis and overtreatment (11). Therefore, surgeons and anesthesiologists often consult with cardiologists during this assessment to reduce serious cardiac events (12).…”
Section: Introductionmentioning
confidence: 99%
“…Arrhythmias associated with Valve Disease 215 • In a study in Rio de Janeiro (Southeastern Brazil) including 1412 candidates for cardiac surgery of any indication, 294 cases with primary valvular heart disease of rheumatic and non-rheumatic etiologies were selected. All patients were aged ≥40 years and had coronary angiography performed.…”
Section: Complications and Associated Diseasesmentioning
confidence: 99%